The Development of the Masaklaw na Panukat ng Loob (Mapa ng Loob). [article]. - Del Pilar, G.
Studies have shown that trait constructs measured by the two earlier Filipino personality inventories and a lexically based Filipino personality research instrument are well represented by the Five-Factor Model (FFM; Katigbak et al., 2002; Church et al., 1997). On this basis, a 188-item instrument that sets out to operationalize the FFM with Filipino trait constructs was developed, with a core of twenty facet scales, each with eight items, and grouped by four for each of the five domains. In six successive item-testing studies, considerations of internal consistency reliability, content validity, keying balance, and factor structure were addressed. While most of the samples across the six item-testing studies came from the national state university in Metro Manila, data for the last study (total N = 576) also included student samples from three other universities (N = 192), as well as an adult sample (N = 192). The reliabilities for the final version of the instrument ranged from .65 to .81, with a mean of .72. Keying balance for sixteen facet scales is perfect or near-perfect, with the remaining four having a balance of 2:6. A Principal Component Analysis of the twenty facet scales showed a clear five-factor structure, with each facet loading on its intended factor. Further work on the Mapa ng Loob, which includes the development of a 50-item short form, an English version, and validation studies, are briefly discussed.